If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation.

−x + 5y = 1
2x + 4y = −4

Respuesta :

-x+5y=1   -x+5y-5y=1-5y  -x=1-5y  -x/-1=1/-1 -5y/-1  x=-1+5y so the expression equivalent to x is -1+5y. Now the substitution

2x+4y=-4                                  -2+14y=-4                        14y/14=-2/14
2(-1+5y)+4y=-4                        -2+2+14y=-4+2                       y=-1/7
-2+10y+4y=-4                               14y=-2
x=-1+5y
x=-1+5(-1/7)  x=-1-5/7    x=-12/7. So x=-12/7 and y=-1/7